Statins regulate kinase signaling by causing changes in phosphorylation, rather than through changes in gene expression or direct inhibition: evidence in colorectal cancer - Lagunas-Rangel, Francisco Alejandro; Jonsson, Jörgen; Jackevica, Ludmila; Fredriksson, Robert; Dambrova, Maija; Schiöth, Helgi B. (Frontiers in Pharmacology, 2025)
IntroductionStatins, widely used for hypercholesterolemia, have shown anticancer properties including induction of apoptosis and ferroptosis, modulation of autophagy, and reprogramming of the tumor microenvironment, making them potential candidates for repurposing in cancer therapy. Although growing evidence suggests that statins may influence kinase signaling, current data remain inconclusive. To better understand this potential mechanism, we investigated the impact of statins on kinase activity.MethodsWe employed an integrative approach combining publicly available RNA-seq and phosphoproteomic datasets with in vitro kinome inhibition profiling. The study assessed the effects of atorvastatin, simvastatin, and cerivastatin across a panel of 400 kinases. Western blot was used to assess whether reduced PI3K phosphorylation was due to mevalonate depletion.ResultsOur analyses revealed that statins primarily influence kinase signaling via alterations in phosphorylation rather than through transcriptional regulation or direct inhibition. Phosphoproteomic data showed a general reduction in kinase phosphorylation, although some kinases exhibited increased activity. Affected kinases were significantly enriched in cancer-associated pathways, including insulin signaling, EGF–EGFR signaling, PI3K/AKT signaling, and the PD-L1/PD-1 immune checkpoint axis. Direct inhibition was observed for two kinases: CAMK1G (IC50 = 8.9 μM) and TSSK1B (IC50 = 3.3 μM). In colorectal cancer cell lines, decreased PI3K phosphorylation was at least partially attributable to mevalonate depletion, a known consequence of statin treatment.DiscussionThese findings suggest that the anticancer activity of statins may be mediated, at least in part, through their ability to modulate kinase phosphorylation and activity. This mechanistic insight supports further exploration of statins as modulators of kinase signaling in oncology.